Phase-Locking Performance of Optical Injection-Locking Evaluated by Coherent Detection - Wahlsten, Martin (My University, 2010)
The phase sensitive fiber optical amplifier (PS-FOPA), has shown potential for several key applications, for example extreme low noise amplification. Furthermore, PS-FOPAs implies strict demands of precise control of phase relations of the input optical waves to the amplifier. This phase-locking of optical waves can be done by utilizing injection-locking, which is a technique currently being used to some extent. In order to gain a deeper understanding of the phase-locking performance of injection-locking, novel coherent time domain measurements has been conducted. Performance measurements are focused on phase variance in time domain. The results agree with theoretical work previously done by Bordonalli et al. Several tradeoffs are identified, amongst them, between PM-to-PM transfer and AM-to-PM transfer. Balancing the injection ratio and locking-bandwidth for minimal phase noise is also concluded to be nontrivial.
Keywords: Fotonik; Photonics